Development Of A Product Remanufacturing Assessment Tool Based On Part Attributes And Features - Din, Muhammad Kamil; Ho, Fu Haw (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Automotive waste is one of the main problems that can be found in waste management especially in developing countries. The purpose of this study is to evaluate the factors and criteria that influencing remanufacturing process and to build an assessment tool that can provide a performance index for automotive parts to undergo remanufacturing process. Analytic Hierarchy Process (AHP) was used in this study in data collection and analyzing data. A questionnaire was produced by three main factors and fifteen sub-criteria criteria, which were subsequently prioritized using the AHP technique. Fourteen participants were involved in answering the questionnaire to evaluate the importance level between all the factors. The participants involved are engineers and academicians. The result finds out that Product development factors gain the highest weightage score which is 0.770, followed by External factors with a score of 0.127 and Internal Factors got the lowest weightage score which is 0.103. Then, the data from the analysis will be used to developed an assessment tool. The assessment tool was validated by three academicians and the tools were found helpful and acceptable. The tools might be used for remanufacturing industries to be used as a guideline to evaluate the automotive parts before undergoing remanufacturing process and improve the remanufacturing process.